The Effect of Superabsorbent Polymer on Fair-Faced Concrete Performance Based on White Cement - Jun Shi; Zhangbao Wu; Jinping Zhuang; Rong Chen; Tongran Zhu; Chenzheng Yuan; Huixia Li (Advances in Civil Engineering)
Introducing superabsorbent polymer (SAP) into white fair-faced concrete can achieve the purpose of internal curing, which is beneficial to the popularization and application of white fair-faced concrete. The effects of the SAP mixture and internal curing water content on the properties of white fair-faced concrete were investigated macroscopically through the indexes, including slump, electric flux, standard cube compressive strength, and tensile splitting strength. The mechanism of these influence laws was further analyzed by scanning electron microscope (SEM). The results show that the slump increases with the increase of SAP content and internal curing water; the incorporation of SAP can significantly reduce the electric flux of white fair-faced concrete and improve its durability; with the increase of SAP admixture and internal curing water content, the compressive strength of white fair-faced concrete decreases, which has a significant impact on the early compressive strength; the addition of SAP is beneficial to the improvement of the tensile properties and tensile-compression ratio of white fair-faced concrete. When the SAP content is 0.2%, and the internal curing water is ten times the mass of SAP, the optimal performance of white fair-faced concrete can be achieved; the water released by the SAP promotes the secondary hydration reaction, which can refine the internal structure of white fair-faced concrete.